Smart as a Global Vision? Exploring Smart in Local District Development Projects. Issue 3 (2nd September 2019) - de Hoop, Evelien; van Oers, Laura; Becker, Sören; Macrorie, Rachel; Spath, Philipp; Astola, Mandi; Boon, Wouter
Abstract: This article studies local enactments of "smart" in and through visions of six smart district development projects. We show that smart cities' framings of the future are inevitably diverse, emerging from local assemblages consisting of a wide array of heterogeneous elements that translate global imaginaries of the smart city to meet local specificities, needs and agendas. We demonstrate that visions may describe the process of district planning and design, the materiality of the envisioned district and the governance of the district; and that smart visions may play three distinct roles – they may act as mobilizers, instrumentally (i.e. as tools to achieve specific sociotechnical goals) and to exclude alternatives. Knowledge forms a key constituent of smart visions, and acts to include some while excluding others. We therefore suggest that further research should focus on the political and controversial construction and use of knowledge in visioning processes.